PENGARUH UKURAN OVARIUM SAPI TERHADAP KUALITAS MORFOLOGI OOSIT YANG DIKOLEKSI SECARA IN VITRO - , PUGUH BUDI SUSILO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The production of embryos using in vitro method which consists of maturation, fertilisationand culture needs qualified oocytes in order to get good embryos. The size of ovarian, the producer of oocytes, which is taken from abbatoir (RPH) is vary from one individu to another. To fulfill the need of oocytes from the abattoir (RPH), ovarian as the primary material required precise and rapid handling. The indirect selection of oocytes could be conduct by examining other organs which have relation to the oocytes quality, and in this research examining the size of the ovarian was the selected way. The purpose of this research was to find out the effects of the size of cowâs ovarian to the quality of oocytes morphology. The ovarians taken from abattoir (RPH) were washed using 0,9% phyciological Nacl which had been added with antibiotics Penicilin 100 IU/ml and Streptomycin 100 Î¼g/ml. Then, the ovarians were classified based on their size. The first group consists of1,0 â 1,9 cm, the second group consists of 2,0 â 2,9 cm and the third group consists of 3,0 â 3,9 cm. Oocytes were collected using aspiration method which used 10 ml spuit and 18 G needle. The observation of the oocytes collection was conduct using stereo microscope and were classified based on the oocytes morphology. The collected data were analyzed using ANOVA. The findings of the research is that quality of oocytes morphology do not have significant variation to the size of cowâs ovarians. The second group produced oocytes with A 34, 25% and B 41,10% quality which was higher than the first group (22,33% and 43, 69%) and the third group (16,53 % and 32,23%). Meanwhile, for the amount of the oocytes A and B quality is higher in the second group (75, 35%). From the data, it can be conclude that the size of cowâs ovarian does not influence to the procentage of the amount of oocytes based on the quality of morphology of A and B oocytes.